1995
DOI: 10.1016/0304-3894(95)00058-3
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of mercury emissions and health risks from a coal-fired power plant

Abstract: Title III of the 1990 Clean Air Act Amendments (CAAA) mandated that the U.S. Environmental Protection Agency (EPA) evaluate the need to regulate mercury emissions from electric utilities. In support of this forthcoming regulatory analysis the U.S. DOE, sponsored a risk assessment project at Brookhaven (BNL) to evaluate methylmercury (MeHg) hazards independently. In the U.S. MeHg is the predominant way of exposure to mercury originated in the atmosphere. In the BNL study, health risks to adults resulting from H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Iodated carbon has been shown to be nearly 100% efficient at removing mercury vapor from gaseous streams. 2,18,19 Hence, to determine if any of the mercury liberated during pyrolysis was not being collected on the gold meshes, an iodated carbon trap was placed after the second gold mesh for the analysis of 200, 400 and 800 ng g 21 coal spikes. Because no mercury was detected in the traps in any trial within experimental detection limits, it was concluded that no mercury breakthrough occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodated carbon has been shown to be nearly 100% efficient at removing mercury vapor from gaseous streams. 2,18,19 Hence, to determine if any of the mercury liberated during pyrolysis was not being collected on the gold meshes, an iodated carbon trap was placed after the second gold mesh for the analysis of 200, 400 and 800 ng g 21 coal spikes. Because no mercury was detected in the traps in any trial within experimental detection limits, it was concluded that no mercury breakthrough occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Coal combustion for the generation of electricity is considered to be a leading anthropogenic source of mercury emissions. [1][2][3] In a 1980 report issued by the National Research Council, mercury was classified an element of 'greatest concern' because of its high toxicity. 4 Owing to the high volatility of elemental mercury and mercury compounds, it is generally accepted that a significant portion of the mercury present in coal is emitted in the stack gases during coal combustion.…”
mentioning
confidence: 99%
“…Hg 0 vapor concentrations utilized in this study were in the range of 24-365 ppb v and were chosen based on the levels present in many industrial processes. 25,54,55 Different concentrations of Hg 0 vapor were obtained by controlling the temperatures of the permeation tube. The mercury gas concentrations tested are relevant to the alumina industry process.…”
Section: Mercury Testing Setupmentioning
confidence: 99%
“…Atmospheric elemental mercury has a half-life of six to twenty-four months thus allowing for long range transport in the atmosphere. Elemental mercury is considered inert due to its relative insolubility in water contributing to global transport mechanisms (Fthenakis et al, 1995;Carpi, 1997;Bergen et al, 1999). Often, deposited mercury in both elemental and oxidized forms is re-emitted back into the atmosphere as a gas, or associated with dust and other particulate matter, providing an additional source term for the total global reservoir flux (Bergen et al, 1999;Environmental Protection Agency, 2003).…”
Section: +2mentioning
confidence: 99%